Food and functional dyspepsia: a systematic review. Issue 3 (15th September 2017) - Duncanson, K. R.; Talley, N. J.; Walker, M. M.; Burrows, T. L.
Abstract: Background: Functional dyspepsia (FD) is a debilitating functional gastrointestinal disorder characterised by early satiety, post‐prandial fullness or epigastric pain related to meals, which affects up to 20% of western populations. A high dietary fat intake has been linked to FD and duodenal eosinophilia has been noted in FD. We hypothesised that an allergen such as wheat is a risk factor for FD and that withdrawal will improve symptoms of FD. We aimed to investigate the relationship between food and functional dyspepsia. Methods: Sixteen out of 6451 studies identified in a database search of six databases met the inclusion criteria of studies examining the effect of nutrients, foods and food components in adults with FD or FD symptoms. Results: Wheat‐containing foods were implicated in FD symptom induction in six studies, four of which were not specifically investigating gluten and two that were gluten‐specific, with the implementation of a gluten‐free diet demonstrating a reduction in symptoms. Dietary fat was associated with FD in all three studies that specifically measured this association. Specific foods reported as inducing symptoms were high in either natural food chemicals, high in fermentable carbohydrates or high in wheat/gluten. Caffeine was associated with FD in four studies, although any association with alcohol was uncertain. Conclusions: Wheat and dietary fats may play key roles in the generation of FD symptoms and reduction or withdrawal eased symptoms. Randomised trials investigating the roles of gluten, FODMAPs (fermentable oligosaccharide, disaccharide, monosaccharide and polyols) and high fat ingestion and naturally occurring food chemicals in the generation of functional dyspepsia symptoms are warranted and further investigation of the mechanisms is now required.